Cytotoxicity of carriers for the delivery of drugs to cancer cells - Divya, Venkataraman (2013)
Although the concept of drug delivery system is old, its application has widened recently. An appreciable progress has been implemented in the treatment of lethal diseases such as cancer, targeting the delivery of drugs as one important aspect. For drug delivery, the carriers to load and unload the drugs should be biocompatible and biodegradable in nature for in vivo applications. To fabricate suitable carriers for targeted and controlled release of drugs, the Layer by Layer(LbL) technique has invoked a great interest in the field of biomedical engineering. LbL method ensures consecutive adsorption of alternatively charged polyelectrolyte pairs on the porous colloidal templates. The choice of polyelectrolyte pairs and the core for the drug delivery application has remained an issue for several years. The main purpose of this project is the study of in vitro cytotoxicity of the carriers to the MCF-7 human breast cancer cell line. The carriers used in this study are polyelectrolyte coated on the porous colloidal templates, the CaCO3 micro particles and hydroxyapatite nanoparticles. The surface characterization study proved the particle stability by zeta potential measurements. Additionally, qualitative study of the internalization of the carrier particles proved successful uptake by the model 3T3 mouse fibroblast cells and the target MCF-7 human breast cancer cells. Also, the extent of cytotoxic response elicited by the target cells on treatment with varying concentration of the carrier particles was studied using the MTT(3-(4, 5-dimethylthiazolyl-2)-2, 5-diphenyltetrazolium bromide) assay. This proved that the concentration of the carriers used were not significantly cytotoxic to the target cells. Thus to conclude, the fabricated carriers are highly biocompatible and suitable for various in vivo applications in the drug delivery system.